About Some Polyfunctional Resources in Political Discourse - Cortés Rodríguez, Luis (2024)
The use of syntactic groups (nominal, verbal, etc.) which, through their repetition, acquire an intensifying value is frequent in any type of discourse and even more so in political discourse. In the two issues analyzed in this article, such repetitions assume simultaneously, together with the most proper function, that of highlighting, several others. In the first of these, the intensifying value is added to the capacity of the syntactic group to initiate a new discursive act; this will facilitate, on the one hand, the fluency of the discourse and, on the other, greater intelligibility by making explicit, through duplication, the antecedent term. In the second issue, the intensification expressed by the reiterated fragment is combined with its condition of closing the act or statement, which greatly enhances the message. We have made use of a corpus that is formed by the speeches issued by the leaders of the four most important parties in Spain during the motion of censure of President Mariano Rajoy, on May 31 and June 1, 2018.